تأثير كمية وموعد الري الإضافي في ديناميكية الإزهار والعقد وتطور الثمار لصنفي التفاح غولدن ديليشيس و ستاركنغ ديليشيس - مخول, جرجس; علي, علي; عثمان, إياد (Latakia University Journal -Biological Sciences Series, 2018)
* شملت الدراسة عشر معاملات لكل صنف وبثلاث مكررات لكل معاملة وبينت النتائج مايلي: - أثّر الري بشكل واضح في زيادة قطر الثمرة حيث بلغ 5.10 سم و 5.53 سم للصنف غولدن ديليشيس عند المعاملة بـ 200 ليتر ماء كل4 أيام في حين لم يتجاوز 4.25 سم و 4.6 سم في الشاهد بدون ري بينما بلغت هذه الزيادة 4.55سم و 5.41 سم في الصنف ستاركنغ ديليشيس عند المعاملة بـ 200 ليتر ماء كل 4 أيام في حين لم يتجاوز 4.05سم 4.98 سم في الشاهد للعامين 2004 و 2005. - أثّر الري بشكل واضح في متوسط وزن الثمرة وخاصة في عام 2005 نتيجة للأثر التراكمي له. وتفوقت المعاملة 200 ليتر كل 4 أيام على بقية المعاملات لكلا الصنفين غولدن ديليشيس و ستاركنغ ديليشيس حيث بلغ متوسط وزن الثمرة ( 111.6غ) و (114.3غ) عامي 2004 و2005 للصنف غولدن ديليشيس و(91.4غ) و(92.5غ ) للصنف ستاركنغ ديليشيس بينما بلغ متوسط وزن الثمرة في الشاهد (74.8غ) و (76.9 غ) عامي 2004 و2005 للصنف غولدن ديليشيس و (69.5غ ) و (73.5 غ) للصنف ستاركنغ ديليشيس وهذه الزيادة في متوسط وزن الثمرة تقدر بـ 48.92% للصنف غولدن ديليشيس و 28.68% للصنف ستاركنغ ديليشيس مقارنة بالشاهد من دون ري كمتوسط لعامي الدراسة. - لم يظهر الري أثراً واضحاً في ديناميكية الإزهار لكلا الصنفين وخلال عامي الدراسة. The study contained ten treatments of each variety with three replicates for each. Treatment and results showed that Fruit diameter was effected clearly by irrigation. It was increased for golden delicious by (5.1 c.m), (5.53 c.m) respectively, when irrigated every four days by 200 liters of water per a tree compared to (4.25 c.m), (4.60 c.m) respectively in the control treatment. However, it was increased for starking delicious by (4.55 c.m), (5.41 c.m) respectively, when irrigated every four days by 200 liters of water per a tree compared to (4.05 c.m), (4.98 c.m) respectively in the control treatment during 2004, 2005. The average weight of fruit was effected by irrigation especially in 2005 for the additive effect. The treatment by 200 liters of water every four days was better than other treatments for golden delicious and starking delicious. It was increased by (111.6 g), (114.3 g) for golden delicious, (91.4 g), (92.5 g) for starking delicious compared to (74.8 g), (76.9 g) for golden delicious and (69.5 g), (73.5 g) for starking delicious respectively in the control treatment during 2004, 2005. The additional irrigation with 200 liters of water per a tree every four days caused increasing of production about 48.92 % for golden delicious and 28.68% for starking delicious respectively in the control treatment during 2004, 2005. Irrigation has no clear effect on flowering for golden delicious and starking delicious during 2004, 2005.